The influence of spiritual intelligence, leadership, and nurse performance at Dustira hospital in Cimahi city - Trismiyanto, Harun Heri; Azmi, Hasna Nuru; Setiawan, Bagas; Arsyika, Adila Tahta (SEAN Institute, 2024)
This study aims to investigate the influence of spiritual intelligence and leadership on nurse performance at Dustira Hospital in Cimahi City. This research employs a quantitative approach with data collection through a questionnaire distributed to nurses at Dustira Hospital. The research sample is obtained through purposive sampling, and data analysis is conducted using regression techniques to evaluate the influence of spiritual intelligence and leadership on nurse performance. The results of this study are expected to provide a better understanding of how spiritual intelligence and leadership contribute to the performance of nurses at Dustira Hospital in Cimahi City. These findings can serve as a foundation for hospital management to develop training and development programs that focus on these aspects, thereby improving the quality of healthcare services provided by nurses. This research is also expected to contribute theoretically to the literature in the field of human resource management in the healthcare sector, particularly in the context of spiritual intelligence, leadership, and nurse performance. Thus, this study provides new insights for the development of policies and management practices in hospitals and the healthcare sector in general.